Explain how to determine the inverse of the function \( f(x) = 2x + 3 \) and demonstrate by finding its graph.
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Extra Insights
To determine the inverse of the function \( f(x) = 2x + 3 \), start by replacing \( f(x) \) with \( y \), giving you the equation \( y = 2x + 3 \). Next, swap \( x \) and \( y \) to find the inverse: \( x = 2y + 3 \). Now, solve for \( y \): \( 2y = x - 3 \) leads to \( y = \frac{x - 3}{2} \). Thus, the inverse function is \( f^{-1}(x) = \frac{x - 3}{2} \). For the graph, plot both functions on the same coordinate plane. The original function \( f(x) \) will be a straight line with a slope of 2, while the inverse function \( f^{-1}(x) \) will also be a straight line with a slope of 0.5. They will reflect over the line \( y = x \), showcasing their inverse relationship in a visually appealing way!